2020
DOI: 10.34257/gjrejvol20is5pg1
|View full text |Cite
|
Sign up to set email alerts
|

Production Decline Prediction of Shale Gas using Hybrid Models

Abstract: Hybrid models have frequently been used for shale gas production decline prediction by manipulating the unique strength of each of the known decline models. The use of a combination of models provides a more precise predicting model for forecasting time series data as compared to an individual model. In this study, the forecasting performance of decline curve hybrid models and ANN-ARIMA hybrid models are evaluated and compared with Arps’, Duong’s, the Power Law Exponential Decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…However, based on the findings from the study on production decline prediction using hybrid models, the results showed that the artificial neural network (ANN), autoregressive integrated moving average (ARIMA), and Arps−power law exponential (Arps−PLE) hybrid rate decline models showed better accuracy. 5 The finding concurred with work conducted by Taskaya-Temizel et al 6 hybrid models, Arps−PLE hybrid decline and ANN−ARIMA hybrid, for shale gas production. The main ideas are to (a) use the goodness-of-fit statistical assessment to evaluate the accuracy of the models, (b) validate the models using the mean absolute percentage error (MAPE) values, and (c) summarizes findings from the research study.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, based on the findings from the study on production decline prediction using hybrid models, the results showed that the artificial neural network (ANN), autoregressive integrated moving average (ARIMA), and Arps−power law exponential (Arps−PLE) hybrid rate decline models showed better accuracy. 5 The finding concurred with work conducted by Taskaya-Temizel et al 6 hybrid models, Arps−PLE hybrid decline and ANN−ARIMA hybrid, for shale gas production. The main ideas are to (a) use the goodness-of-fit statistical assessment to evaluate the accuracy of the models, (b) validate the models using the mean absolute percentage error (MAPE) values, and (c) summarizes findings from the research study.…”
Section: Introductionsupporting
confidence: 86%
“…A proposed hybrid model approach was examined since studies conducted have proved its higher accuracy. However, based on the findings from the study on production decline prediction using hybrid models, the results showed that the artificial neural network (ANN), autoregressive integrated moving average (ARIMA), and Arps–power law exponential (Arps–PLE) hybrid rate decline models showed better accuracy . The finding concurred with work conducted by Taskaya-Temizel et al whereby in certain conditions the single-model methodology can outperform the hybrid models.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation